Design of a compact and sustainable physical-chemical system for drinking surface waters in remote areas of Arequipa-Perú - Gordillo Pinto, Romel; Aguilar Franco, José Alberto (Nexo Revista Científica, 2022)
A physicochemical treatment system for surface water has been designed and manufactured to provide drinking water to remote areas that do not have access to basic service. The system consists of four main units; the first: pre-treatment, it filters the particles and sediments present in the water from a nearby surface source; the second unit: primary treatment; doses chemical inputs for coagulation and generation of flocs to sediment the particles as sludge and remove them later; the third secondary treatment unit; Filters microscopic particles and microbial or pathogenic agents and water is chlorinated to provide the required drinking quality according to regulations. The fourth unit, energy generation; It takes advantage of solar radiation and converts it into electrical energy so that the equipment operates properly. The results indicate that it is feasible to implement the proposed system to provide water suitable for human and in compliance with the standards of the current national regulations intended mainly for vulnerable communities.